2002
DOI: 10.1080/00221320209598689
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Coping Resources and Satisfaction With Life Among Middle-Aged, Young-Old, and Oldest-Old Adults

Abstract: The authors examined age differences in perceived coping resources and satisfaction with life across 3 older-adult age groups (45-64, 65-74, and 75 years and older). The 98 participants represented healthy, socially active, community-residing adults. Group comparisons were made on 12 individual coping scales, and an overall coping resource effectiveness score was computed. No significant differences were found for 11 of the coping resources or for overall coping resource effectiveness. Similar consistencies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 18 publications
5
64
1
5
Order By: Relevance
“…In our hierarchical multivariate regression models, depressive symptoms and trauma symptoms were inversely associated with resilience, as expected. Also, older age was associated with increased resilience, consistent with prior studies demonstrating an association between greater resilience and increasing age (Hamarat, Thompson, Steele, Matheny, & Simons, 2002). However, while semantic verbal fluency (Animals), processing speed (WAIS-III Symbol Search), and non-verbal memory (BMVT delayed recall) continued to predict occupational resilience when partialling out the effects of age, education, HIV status, depressive and posttraumatic stress symptoms, the direction of these effects were in the opposite direction than what we hypothesized, such that lower neurocognitive scores were associated with greater resilience.…”
Section: Discussionsupporting
confidence: 87%
“…In our hierarchical multivariate regression models, depressive symptoms and trauma symptoms were inversely associated with resilience, as expected. Also, older age was associated with increased resilience, consistent with prior studies demonstrating an association between greater resilience and increasing age (Hamarat, Thompson, Steele, Matheny, & Simons, 2002). However, while semantic verbal fluency (Animals), processing speed (WAIS-III Symbol Search), and non-verbal memory (BMVT delayed recall) continued to predict occupational resilience when partialling out the effects of age, education, HIV status, depressive and posttraumatic stress symptoms, the direction of these effects were in the opposite direction than what we hypothesized, such that lower neurocognitive scores were associated with greater resilience.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies tell us that LS has been found to increase with age, but no study has previously investigated older age groups, and the difference that impaired vision can make in LS. Others have also found that older age groups have higher levels of LS (Hamarat et al 2002;Hileras et al 2001). Hamarat et al found that among healthy, active adults, aged 45?, the oldest old reported LS at least as good as, and better than the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Heyl and Wahl (2001) found that both the vision impaired and sighted groups reported a decline in overall LS, however, several studies have found that LS actually improved with age in those aged 65? (Hamarat et al 2002;Hileras et al 2001). Moreover, Diener (1984) found LS generally improves after about age 40.…”
Section: Introductionmentioning
confidence: 99%
“…23 In two studies among older adults, level of life satisfaction was found to be the same across all ages. 24,25 Furthermore, older age has been seen to be positively associated with family life and financial and vocational situation. 23 In contrast, other studies have suggested caution when comparing life satisfaction with different age groups; 23 however, this uncertainty might be due to SWLS items 4-5, which have been shown to be sensitive to age, 12 whereas SWLS items 1-3 have been found to be insensitive to age.…”
Section: Discussionmentioning
confidence: 99%